The role of non-profit organizations in teacher education – case study - Domiter, Małgorzata; Marciszewska, Anna (Economics of the 21st Century, 2017)
The idea of life-long education and self-improvement relates also to educating the “perpetrators” of education, namely teachers. The European Union is a witnesses to a discussion about teachers’ competences and qualifications. The European Commission has suggested common European principles referring to the profession of teacher and education models. The Polish teacher education system is fully compatible with the requirements of the European educational policy. However, in the opinion of teachers it does not solve all the problems and does not completely fulfill their educational needs. For this reason, nonprofit organizations have addressed teacher’s expectations and fulfilled a gap created in the teacher education system. How have they managed? This paper will deal with this question. It presents a non-profit organization from Lower Silesia that, in the years 2009-2014, completed five projects with a total value of PLN 2,464,136.79, for the benefit of 1321 teachers working in the area of Lower Silesia Province. The presented article supplements the deficiencies in scientific literature which is characterized by the lack of complex scientific publications focused on the assessment of the suitability of teacher education by non-profit organizations in light of both Polish and European requirements
Ekonomia XXI Wieku = Economics of the 21st Century, 2017, Nr 2, s. 39-55
Keywords: teacher education; vocational training; non-profit organisations; subsidies; European projects; kształcenie nauczycieli; doskonalenie zawodowe; organizacje non profit; dotacje; projekty europejskie